CONSTRUCTING THE INTEGRATION GUIDEBOOK OF CHINESE VOCAL FOLK AND YU OPERA FOR TEACHING STUDENT AT ZHOUKOU VOCATIONAL AND TECHNICAL COLLEGE - Li, Wang; Charoensloong, Thitinun (Asia Pacific Journal of Religions and Cultures, 2023)
The research topic is “Constructing the Intergration Guidebook of Chinese Vocal Folk and Yu Opera for Teaching Students at Zhoukou Vocational and Technical College” The purpose of this study is to study a change in the learning situation of ethnic vocal music and Henan Opera students in Zhoukou Vocational and Technical College under the new teaching guide, and to use qualitative and quantitative research methods to explore. Through the interview of experts, the key informant assessment is reasonable, student sampling questionnaire analysis, the key informant assessment of the feasibility, and their learning, to develop Zhoukou Vocational and Technical College National Vocal Music and Henan Opera has been innovating teaching guide, learning to do a theoretical study, finally concluded that the feasibility of the guide book whether to meet the needs of students at the current level. Research has proved that the guidebook is helpful to students’ learning and is a more useful guide tool. According to the suggestions of experts, teachers should use the corresponding teaching framework and theory combined with practical teaching to improve students’ learning efficiency. The course lasts 18 weeks, with a total of 36 hours per semester. By comparing the results of the pretest and the posttest, the researchers verified the effectiveness of the teaching guide for folk vocal music and Henan opera in vocational-technical colleges.